Estimación de las componentes de varianza en modelos lineales mixtos con estructura de bloques ortogonal conmutativa - Ferreira, Sandra S.; Ferreira, Dário; Nunes, Célia; Mexia, João T. (Revista Colombiana de Estadística, 2013)
Segregation and matching are techniques to estimate variance components in mixed models. A question arising is whether segregation can be applied in situations where matching does not apply. Our motivation for this research relies on the fact that we want an answer to that question and to explore this important class of models that can contribute to the development of mixed models. That is possible using the algebraic structure of mixed models. We present two examples showing that segregation can be applied in situations where matching does not apply.